Health Information: A Case Report of "Unknown" Hepatitis in Indonesia - Elanda Fikri; Yura Witsqa Firmansyah (Journal of Health Science and Prevention, 2022)
Hepatitis is a disease that attacks the liver by inflammation. The Hepatitis virus is the most common agent causing hepatitis. Globally, hepatitis that often occurs in the world is hepatitis A-E. Recently, reported a new case of hepatitis with unknown aetiology. On 12 May 2022, reported by the European Center for Disease Prevention and Control, the reported cases of "unknown" hepatitis in children aged under 10 years in the UK were 176 cases. Other countries outside the EU/EEA and the United Kingdom reported that on May 19, 2022, reports of "unknown" hepatitis cases in children reached 313 cases, identified from 16 countries. The Ministry of Health of the Republic of Indonesia released on May 17, 2022, a total of 14 cases in Indonesia, with details of probable case and 13 pending classification. As of May 19, 2022, reports of deaths due to "unknown" hepatitis cases reached six. This article's objectives to disseminate health information regarding case reports of “unknown” hepatitis, case symptoms, and prevention and control efforts in Indonesia so that it does not become an outbreak. To prevent and control "unknown" hepatitis in Indonesia, the Ministry of Health of the Republic of Indonesia conducts surveillance and therapeutic efforts